Optimizing the physical parameters of polycaprolactone-gelatin-polydimethylsiloxane composite nanofiber scaffold for tissue engineering application. (April 2022) - Dehghan, Mahdieh; Nikukar, Habib; Mehrizi, Mohammad Khajeh
A lot of research has already been conducted on tissue engineering as it can have the potential for organ and tissue regeneration and repair. Research on the proliferation of cells on the scaffolds, which are material-based structures in the extracellular matrix, increased efficiency of 3D cultures. In this study, the stages of preparing a nanofiber scaffold with different ratios of three polymers of Polycaprolactone/Gelatin/Polydimethylsiloxane (PCL/G/PDMS) which is biodegradable, non-toxic and biocompatible are explained for tissue engineering and then fibroblast cells cultivation are discussed. The morphology, porosity and hydrophilicity of the prepared scaffolds were evaluated by scanning electron microscope (SEM), the liquid displacement method, water contact-angle measurements respectively. The cell growth and proliferation on scaffolds were counted by Digimizer © software. Then morphology, porosity and hydrophilicity of scaffolds and cell growth and proliferation on scaffolds were optimized by Response Surface Methodology (RSM). The results show that PCL/G/PDMS electrospun nanofibers can be used for tissue engineering applications. The purpose of this scaffold is design a scaffold for elastic tissue engineering, especially uterine tissue, which will be discussed in the following articles.